SAT0460 Long-term immune protection following pneumococcal 13-valent/23-valent polysaccharide vaccine in systemic lupus erythematosus (SLE). (12th June 2018) - Goulenok, T.; Bahuaud, M.; Francois, C.; Alexandra, J.-F.; Aucouturier, P.; Hurtado-Nedelec, M.; Moins, H.; Batteux, F.; Papo, T.; Sacre, K.
Abstract : Background: Systemic lupus erythematosus (SLE) patients are at increased risk for Streptococcus pneumoniae infection. Although pneumococcal vaccination is an attractive method to prevent invasive pneumococcal infection, vaccination coverage remains dramatically low in SLE. Moreover, the efficacy of vaccination may be reduced in SLE patients and sequential pneumococcal vaccination using new conjugated pneumococcal vaccines in combination with 23-valent pneumococcal polysaccharide vaccine (PPV23) is now advocated. Objectives: We aimed to determine the efficacy of the prime-and-boost vaccination strategy using the 13-valent pneumococcal conjugate (PCV13) and 23-valent polysaccharide (PPV23) vaccines in SLE. Methods: Consecutive SLE patients admitted from April to December 2015 in our daycare hospital unit (Paris, France) were enrolled to receive PCV13 vaccine followed by PPSV23 vaccine 8 weeks later. Immune protection, defined by an antigen-specific IgG concentration ≥1.3 µg/mL for at least 70% of 7 pneumococcal serotypes (4, 6 B, 9 V, 14, 18 C, 19 F, 23 F), was assessed at baseline, 2 and 12 months. The primary endpoint was immune protection 12 months (long-term) after PCV13 shot. Results: 37 consecutive adult SLE patients admitted in our daycare hospital unit (Department of Internal Medicine, Bichat Hospital, Paris, France) were screened for pneumococcal vaccination. Among them, 8 patients refused to be vaccinated, 7 patients accepted the vaccination but refused to complete the 12 months immune response follow up and 1 patient had already been vaccinated against pneumococcal infection. Eventually, 21 (40 25–75 years; 85.7% female) SLE patients were included in the study and received the sequential PCV13/PPV23 pneumococcal vaccines. Only 12 patients (57.1%) reached the primary endpoint. Nine patients had no long-term protection with a seroconversion that never (n=4, not protected, NP) or only transiently (n=5, short-term protected, STP) occurred. B-cells defects and immunosuppressive treatment were associated with the NP status. A lower IgG2 serum level and a higher ratio of pre-germinal/post-germinal centre B cells were associated with the STP status. The serotype 19 F IgG titer measured 2 months after PCV13 had the best ability (sensitivity of 100% [95% CI: 47.8–100]; specificity of 91.7% [95% CI: 61.5–99.8]) to predict long-term protection. Conclusions: The benefit of sequential PCV13/PPV23 vaccination in SLE is limited. Several factors are associated with long-term immune protection and may help to design selective schedule strategy and/or new vaccines. Disclosure of Interest: None declared